Tatiana : an Arkady Renko novel - Smith, Martin Cruz, 1942- (Simon & Schuster, 2013)
"In Tatiana, Smith delivers his most ambitious and politically daring novel since Gorky Park. When the brilliant and fearless young reporter Tatiana Petrovna--based on the real-life journalist Anna Politkovskaya--falls to her death from a sixth-floor window in Moscow in the same week that notorious mob billionaire Grisha Grigorenko is shot in the back of the head, Renko finds himself on the trail of a mystery as complex and dangerous as modern Russia itself. The body of an elite government translator shows up on the bleak sand dunes of Kalingrad and the possession he was killed for is nothing but a cryptic notebook with drawings of animals and symbols. A frantic hunt begins to locate and decipher this notebook, a copy of which falls into the hands of Zhenya, the closest thing Renko has to a son--who does not realize that the document will put his life in grave danger. In a fast-changing and lethal race to uncover what this translator knew, and how he planned to reveal it to the world, Renko makes a startling discovery that propells him deeper into Tatiana's past--and, at the same time, paradoxically, into Russia's future. In Tatiana, "the master of the international thriller" (New York Times) draws on his four decades of experience to create the most compelling heroine of his career and the most accurate, damning portrait of modern Russia in contemporary literature, one in which the courageous are never safe, and the corrupt are never content, no matter which side they're on"--